HIDROLISIS Eucheuma cottonii DENGAN ENZIM K-KARAGENASE DALAM MENGHASILKAN GULA REDUKSI UNTUK PRODUKSI BIOETANOL - Mustika Zelvi, Ani Suryani, dan Dwi Setyaningsih (Department of Agroindustrial Technology, Bogor Agricultural University, 2017)
Bioethanol is one of the renewable resources derived from sugar fermentation process of carbohydrate substance with microorganismaid. Hydrolysis is the stage to get the simple sugar and is done with using k-carragenasethat is obtained from the isolation result of marine microbe in E.cottonii’s habitat. The objectives of this research were to gain time hydrolysis to produce the enzyme activity and reducing sugar highs by k-karagenase and to determine the best of the substrate concentration and k-carragenasein producing a reduction sugar and the highest ethanol. The research steps was started from isolate rejuvenation of IH22 microbe, enzyme production of crudeextraction k-carragenase and 80% acetone precipitation, determination of the hydrolysis timeand activity of k-carragenase. The next step was the substrate hydrolysis with amounts of 6%, 9%, and 12% (b/v) solids, by enzyme from acetone concentrations of 0%, 2.5%, and 5% (v/v) and then they were fermented for six days with the S.cereviseaeadapted yeast extract. Thek-carragenasse highest enzyme activity was obtained in incubation for 30-60 minutes while the highest reduction sugar was obtained inhydrolysis time for 120 minutes. During the hydrolysis,12% substrate concentration generated the highest reduction sugar and whole sugar of 3.21% and 9.89%, respectively, while 9% substrate with 5% enzyme treatment contained1.49% reduction sugar and 2.75% whole sugar, which was the best substrate in producing ethanol during fermentation process of 1.23% (v/v) and 0.82% (b/v) with 55.78% substrate efficiency and 70.44% fermentation efficieny.Keywords : bioethanol, Eucheuma cottonii, k-carragenasse, S.cerevisiae